Re-forming Judaism: moments of disruption in Jewish thought - Davids, Stanley M.; Hochman, Leah (Central Conference of American Rabbis, 2023)
"Throughout Jewish history, revolutionary events and subversive ideas have burst onto the scene, transforming everything in their path. Re-forming Judaism seeks to explore these ideas-and the individuals behind them-by delving into historical disruptions that led to lasting change in Jewish thought"--